Sprejem bolnika v enoto intenzivne terapije po operaciji na odprtem srcu - Čepon, Vera (Obzornik zdravstvene nege, 1983)
Following open heart surgery patients are admitted to the Intensive Care Unit where continuous monitoring of their vital function and proper medical care are provided. The paper describes the transport and the admission of these patients, the ICU monitoring equipment, some important medico-technical interventions and the tasks of the nursing personnel.